Tingkat Perkembangan Motorik Kasar dengan Keparahan Stunting (Studi pada Anak Sekolah Dasar): Perkembangan Motorik Kasar dengan Tingkat Keparahan Stunting (Studi pada Anak Sekolah Dasar) - Puji Afiatna; Indri Mulyasari (Universitas Airlangga, 2022)
Background: The high prevalence of stunting, which is a linear growth failure in school-aged children, has an impact on gross motor development. The parenting style and feeding style influences children's growth and development. Objectives: To analyze the correlation gross motor development with severity of stunting in primary school children. Methods: This research is a cross sectional research on 91 children with stunting who were selected consecutively in primary school at Kecamatan Ungaran Barat, Kabupaten Semarang. The data collection was conducted by doing anthropometric measurement and gross motor development (locomotor and object control). The correlation between two categorical variables wastested by conducting Rank Spearman test. Results: The nurtritional status of stunting in 84 (92,3%) children with moderate stunting and 7 (7,7%) children with severe stunting. The gross motor development of children under the average was 46,1%, with the average score of intelligence of 91,92. In bivariate analysis, stunting were not significantly related to Gross Motor Quotient (GMQ) level (p=0.241; p>0.05). Conclusions: The nutritional status of stunting is related to the low score of children's gross motor development so that it is necessary to improve nutrition and provide stimulus to train gross motor skills by parents or schools.